2015
DOI: 10.17979/reipe.2015.0.13.319
|View full text |Cite
|
Sign up to set email alerts
|

Estudio cualitativo en un grupo de estudiantes ourensanos/as sobre el fenómeno del Sexting

Abstract: ResumenEl Sexting es el envío, recepción y reenvío de fotografías, vídeos y/o textos de tipo erótico-sexual, a otras personas a través de teléfonos móviles, tablets, redes sociales u otros medios informáticos. El objetivo de esta investigación consistió en identificar comportamientos, motivaciones y percepciones de los/as adolescentes sobre el Sexting. La muestra está formada por 47 adolescentes de la ciudad de Ourense, con un rango de edad de 15 a 18 años. A través de una metodología cualitativa, se observa q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 15 publications
(15 reference statements)
0
4
0
5
Order By: Relevance
“…Adults and young adults pointed out sexting as an affective manifestation inside of relationships, being part of it, and the studies with this population were not restricted to risk evaluation, which suggests investigations with more accuracy in this field. Otherwise, it was shown a greater perception of risk among adolescents (Alonso-Ruido et al, 2015;Mejía-Soto, 2014). The adolescents indicated motivations that suggest the influence of pairs, such as jokes, friends, or partners' pressure or desire to be at risk.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Adults and young adults pointed out sexting as an affective manifestation inside of relationships, being part of it, and the studies with this population were not restricted to risk evaluation, which suggests investigations with more accuracy in this field. Otherwise, it was shown a greater perception of risk among adolescents (Alonso-Ruido et al, 2015;Mejía-Soto, 2014). The adolescents indicated motivations that suggest the influence of pairs, such as jokes, friends, or partners' pressure or desire to be at risk.…”
Section: Discussionmentioning
confidence: 99%
“…The research revealed that young people do not consider themselves sexting practitioners, although they sext. The most-reported motivations to sexting were: pressure from partners or peers; being drunk; the desire to take risks; curiosity; sending pictures as jokes; not comprehending the pictures or messages as sexting; calling out for attention; being bored; to excite the other person; fashion/hype among younger people; the influence of movies (Alonso-Ruido et al, 2015;Mejía-Soto, 2014;Walker et al, 2013). The pressure to engage in sexting was a meaningful result of three studies and gender differences on the topic were pointed.…”
Section: Category 1: Motivations For Sexting and Perceptions About Thmentioning
confidence: 99%
See 2 more Smart Citations
“…Este término alude al intercambio de contenidos erótico-sexuales a través de tecnologías y medios informáticos, principalmente teléfonos móviles e Internet. Incluye el envío, recepción y reenvío de fotografías, vídeos o mensajes de texto sexualmente explícitos o implícitos (Alonso-Ruido, Rodríguez-Castro, Pérez-André y José-Magalhães, 2015;Hinduja y Patchin, 2012;Lenhart, 2009) producidos por el propio protagonista (McLaughlin, 2010;Pérez et al, 2011).…”
Section: Introductionunclassified